Synoecnema watinagii (Drilonematoidea: Ungellidae: Synoecneminae), a new nematode species parasitic in earthworms from the Philippines with the first molecular and SEM data for the genus - Ivanova, Elena S.; Sumaya, Nanette Hope N.; Spiridonov, Sergei E. (Zootaxa, 2015)
A new species of the genus Synoecnema—S. watinagii sp. n.—is described and illustrated. The species is characterized by its small size, lack of sexual dimorphism apart from sexual characters, males with pericloacal disk, females with anterior vulva position and lacking an anus, and similar caudal organs in both sexes in the shape of long, deep slits on the surface of the posterior half of body. Sequences of D2-D3 LSU and SSU rDNA and SEM images were obtained for the first time for the genus Synoecnema. Phylogenetic analysis of these sequences supported the validity of the genus and elucidated its relationships within Synoecneminae and Drilonematoidea. The earthworm host was characterized by its CoxI mt DNA sequence.